SQ3R STRATEGY IN TEACHING READING - Luh Widiani (Program Studi S1 Pariwisata, Sekolah Tinggi Pariwisata Mataram, 2021)
This research was aimed: To find out significant effect of using SQ3R in teaching reading at the eighth-grade students of SMPN 1 Buer. The kind of this research was quantitative research. The sample of this research was the eighth-grade students of SMPN 1 Buer that consist of 60 students. The instrument of collecting data used test which was 25 multiple choice items. In this research, the researcher gave a treatment and prepared a test in form of multiple choices to look for the effect of using SQ3R strategy. The result of the data analysis indicated that the students of SMPN 1 Buer attained high score on the post test for experimental group who were treated by using SQ3R strategy. It was provable that t-test was higher than t-table, which was the value of t-test was 1.733 and t-table in df 0.05 was 1.671. It means that the use of SQ3R strategy gave a significant effect in teaching reading at the eighth-grade students of SMPN 1 Buer. It was proven by the lowest and highest score in pre-test for experimental group, they were 28 and 60 and posttest were 32 and 72. For the control group in the pre-test gained the lowest and the highest score were 28 and 60 and posttest in lowest and highest scores were 28 and 60. Then, the result of hypothesis testing that the alternative hypothesis was accepted. In other words that teaching reading using SQ3R strategy at the eighth-grade students of SMPN 1